Challenges for the prevention of hypertension among international migrants in Latin America: prioritizing the health of migrants in healthcare systems - Isabel Rada; CABIESES VALDES, BALTICA BEATRIZ (My University, 2024)
Among the health priorities of international migrants, non-communicable diseases such as hypertension are of major interest due to their increasing prevalence, mainly in low- and middle-income countries. Previous evidence has reported a significant risk of hypertension in international migrants derived from multiple exposures during the migration process and at the destination, such as living conditions, health literacy and access to preventive services. Also, poorer disease control has been found compared to the local population. Considering existing deficiencies in access and use of healthcare services related to hypertension prevention and continuity of care of migrants globally, we aimed to offer a Latin American perspective of the challenges faced by international migrants residing in Latin America in accessing hypertension preventive care from a human rights, equity, and universal primary healthcare approaches. From a health systems perspective, we conducted a scoping review of scientific literature on hypertension prevention and control among international migrants in Latin America and the Caribbean. Based on the findings, we discuss the potential influence of migration and health policies on healthcare systems and individual and structural barriers to healthcare access, including lack of insurance, linguistic barriers, limited intercultural competence, and geographical and financial barriers. From existing evidence related to hypertension, we highlight the particular healthcare needs of migrants and their implications for regional public health goals. This aligns with promoting culturally tailored interventions considering the migration process, lifestyle patterns, structural vulnerabilities, and gender particularities in hypertension prevention, diagnosis, and treatment. We advocate for developing universal, voluntary, and systemic regional screening and disease control initiatives in Latin America for hypertension and other chronic conditions.
Keywords: health systems; hypertension; latin america; migrants; prevention; ethnicity; health services accessibility; hispanic or latino; humans; latin america; transients and migrants; ethnicity; health care access; hispanic; human; migration; south and central america